Factors influencing breastfeeding practices in China: A meta‐aggregation of qualitative studies. Issue 4 (6th August 2021) - Wu, Wei; Zhang, Jian; Silva Zolezzi, Irma; Fries, Lisa R.; Zhao, Ai
Abstract: The World Health Organization recommends that women exclusively breastfeed until their babies are 6 months old and continue to breastfeed while introducing complementary foods. A meta‐aggregation methodology was used to systematically review and synthesise the qualitative studies on factors influencing breastfeeding practices of healthy Chinese women in Greater China. English and Chinese databases were searched to identify peer‐reviewed qualitative studies (published 2008–2019). Relevant data were extracted, and key themes related to factors influencing breastfeeding practices were identified. Of 7587 articles identified, 22 qualitative studies met inclusion criteria for the review, 10 of which were published in Chinese. A total of 87 themes were extracted from all included studies and classified into 9 subcategories: government enactment of policies, implementation of policies in workplaces, social expectations, social support, medical and health services, services with Chinese characteristics, breastfeeding and pumping facilities, maternal perceptions of breastfeeding and self‐efficacy to breastfeed. The nine subcategories were then grouped into four categories. Potential effect associations among these influence factors of breastfeeding practices emerged from categories and subcategories. Family members' influence on breastfeeding motivation and self‐efficacy suggest a potential benefit of breastfeeding promotion interventions targeting the whole family. The role of primary care should be fully exploited in breastfeeding promotion, including both prenatal education and post‐partum visits. Standardising the training and qualifications of maternity matrons ( yuesao ) and folk breastfeeding specialists ( cuirushi ) can promote evidence‐based approaches to facilitating breastfeeding during the confinement period. Increased availability of breastfeeding and pumping facilities in the workplace would facilitate continuing breastfeeding after returning to work.